Contrasting water use of two Eucalyptus clones across a precipitation and temperature gradient in Brazil - Hubbard, Robert M.; Carneiro, Rafaela Lorenzato; Campoe, Otavio; Alvares, Clayton A. [UNESP]; Figura, Marco Aurélio; Moreira, Gabriela Gonçalves (Elsevier, 2020)
Eucalyptus plantation productivity has increased 4-fold across Brazil as a result of improved genetic selection and intensive silviculture. However, the rate of productivity improvements is slowing and suggests increased production will require planting in areas that have never been previously planted with Eucalyptus with uncertain impacts on local water supplies. This study compares water use and water use efficiency between a drought resistant (E. grandis × E. camaldulensis) and high productivity Eucalyptus clone (E. urophylla) across three sites (dry, mesic and wet) spanning a two-fold precipitation gradient (~600–1350 mm y−1) in Brazil. Each site included a 30% reduced rainfall treatment for each clone to investigate within site response to reduced precipitation. We found that the drought resistant clone used as much or more water than the high productivity clone at all three sites. The drought resistant clone transpired almost 20% percent more water than the high productivity clone at the dry site (3.7 vs. 3.0 m3 y−1) while water use between clones did not differ at the mesic (4.6 vs 4.0 m3 y−1) and wet site (4.0 vs 4.5 m3 y−1). The high productivity clone transpired 54, 46 and 37% of annual precipitation at the dry, mesic and wet sites respectively while the drought resistant clone consumed 67, 47 and 31% of annual precipitation from the dry to the wet site. Although the rain reduction treatments did not impact annual water use for either clone at the dry and mesic sites, there were some differences at a subannual timescale. Rain reduction treatments at the dry site lowered transpiration in the driest, hottest three months for the high productivity clone by 25–32%. Rainfall reduction led to lower water use by the drought resistant clone for only one month during the dry season (18%). The high productivity clone transpired less water (24–26%) in the rainfall reduction treatment at the mesic site during three months and the drought resistant clone transpired 18 and 20% less water in the rainfall reduction treatment during two months. Rainfall reduction reduced annual transpiration by 59% for the high productivity clone at the wet site. Average water use efficiency of the drought resistant clone was almost 70% lower than the high productivity clone at the dry and mesic sites (~5.2 vs. 1.5 kg m−3 y−1) and was due to the combination of low growth and high water use. Higher than expected growth by the drought resistant clone at the wet site resulted in similar water use efficiency between clones (6.3 vs. 5.8 kg m−3 y−1). We discuss potential implications of our findings and highlight several lines of evidence that suggest the drought resistant clone in this study allocates a greater proportion of gross primary productivity below ground allowing it to access deeper reserves of soil water during dry periods. Our results suggest that decisions to plant drought resistant clones in drought prone areas should be carefully considered and also highlight the need for more research on water use and drought tolerance strategies for Eucalyptus clones bred for more arid areas in Brazil.
Keywords: Drought tolerance; Forest management; Plantation management; Sapflow; Transpiration; Water use efficiency